ENGAGING MINDS: EXPLORING STUDENT PREFERENCES IN GAMIFIED LEARNING - Pinn Tsin Isabel Yee (PUPIL: International Journal of Teaching, Education and Learning, 2025)
As educators explore innovative methods to foster student engagement and comprehension, gamified learning platforms have gained considerable attention. This study investigates the effectiveness of two popular gamification tools in education, focusing on their impact on student engagement, learning retention, and overall preferences. Data was gathered from Monash University Foundation Year students enrolled in Chemistry through standardized feedback instruments. The participants represented a diverse student population, consisting of local and international students from urban backgrounds. Findings indicate that the gamified platform, Blooket is favored by students for its ability to enhance understanding (42%), improve information retention (46%), and clarify complex concepts during lessons (46%). Furthermore, Blooket stood out as the preferred platform during class activities (54%), offering ease of use (39%) and a high engagement factor (58%). Students also reported finding Blooket more enjoyable, with 65% stating that it made learning more fun, while 49% felt it motivated them to participate actively. Qualitative feedback highlighted Blooket’s competitive elements, which students believe contribute positively to their grasp of Chemistry. The findings suggest that Blooket holds promise as a tool for improving learning engagement, and offers an accessible interface for diverse learning styles. Future research could expand on the benefits of gamification by exploring other learning contexts and assessing the long-term impact of such platforms on knowledge retention and student performance. This study reinforces the role of gamified learning as a beneficial supplement to traditional educational methods.